A possible mechanism of antitumor activity of 5 (5’,6’ benzocoumaroyl-3’)-methylaminouracil in vivo - Kopylchuk, H.P.; Shmarakov, I.O.; Marchenko, M.M. (Experimental Oncology, 2007)
Aim: To analyze possible mechanisms of anticancer activity of hydrobromide 5-(5’,6’-benzocoumaroyl-3’)-methylaminouracil (BCU) in vivo. Methods: BCU was administered at the dose of 6 mg/kg for seven days to rats bearing Guerin carcinoma (Gc). Interaction of BCU with DNA isolated from Gc cells was analyzed by electrophoresis and spectrophotometry. Results: It has been shown that BCU administration resulted in chromatin condensation, nuclei picnosis, increase of the DNase activity and the appearance of high-molecular DNA fragments in Gc cells. Conclusion: BCU is shown to be able to interact directly with DNA molecules with the formation of stable complexes.